A Biomimetic 3D‐Self‐Forming Approach for Microvascular Scaffolds. Issue 9 (1st March 2020) - Zhang, Liucheng; Xiang, Yi; Zhang, Hongbo; Cheng, Liying; Mao, Xiyuan; An, Ning; Zhang, Lu; Zhou, Jinxiong; Deng, Lianfu; Zhang, Yuguang; Sun, Xiaoming; Santos, Hélder A.; et al.
Abstract: The development of science and technology often drew lessons from natural phenomena. Herein, inspired by drying‐driven curling of apple peels, hydrogel‐based micro‐scaled hollow tubules (MHTs) are proposed for biomimicking microvessels, which promote microcirculation and improve the survival of random skin flaps. MHTs with various pipeline structures are fabricated using hydrogel in corresponding shapes, such as Y‐branches, anastomosis rings, and triangle loops. Adjustable diameters can be achieved by altering the concentration and cross‐linking time of the hydrogel. Based on this rationale, biomimetic microvessels with diameters of 50–500 µm are cultivated in vitro by coculture of MHTs and human umbilical vein endothelial cells. In vivo studies show their excellent performance to promote microcirculation and improve the survival of random skin flaps. In conclusion, the present work proposes and validifies a biomimetic 3D self‐forming method for the fabrication of biomimetic vessels and microvascular scaffolds with high biocompatibility and stability based on hydrogel materials, such as gelatin and hyaluronic acid. Abstract : Inspired by drying‐driven curling of apple peels, hydrogel‐based micro‐scaled hollow tubules are proposed for biomimicking microvessels with diameters of 50–500 µm, which promote microcirculation and improve the survival of random skin flaps. A 3D‐shape‐morphing technique is of great flexibility and potential to lay the foundation for the construction of complex vascular networks, such as Y‐branches, anastomosis rings, and triangle loops.